2021
DOI: 10.3390/min11050486
|View full text |Cite
|
Sign up to set email alerts
|

Combined Influence of Low-Grade Metakaolins and Natural Zeolite on Compressive Strength and Heavy Metal Adsorption of Geopolymers

Abstract: Metakaolins (MKs) prepared from low-grade kaolins located in the Alvarães (A) and Barqueiros (B) regions of Portugal were used as the aluminosilicate source to compare their effect on the compressive strength and heavy metal adsorption of geopolymers. Natural zeolite, an inexpensive, efficient adsorbent, was used as an additive in formulations to enhance geopolymers’ adsorption capacities and reduce MK utilization’s environmental footprint. Geopolymers were synthesized with the replacement of MK by zeolite up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The third cluster is composed of G4 and G6, with a positive correlation with C Ra-226 and I α in terms of PC1, and a negative correlation with all the variables in terms of PC2. The different behavior evidenced by the PCA algorithm can be strictly dependent on the chemical composition and mineralogical nature of the investigated raw building materials for underground parking lots [ 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third cluster is composed of G4 and G6, with a positive correlation with C Ra-226 and I α in terms of PC1, and a negative correlation with all the variables in terms of PC2. The different behavior evidenced by the PCA algorithm can be strictly dependent on the chemical composition and mineralogical nature of the investigated raw building materials for underground parking lots [ 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The different behavior evidenced by the PCA algorithm can be strictly dependent on the chemical composition and mineralogical nature of the investigated raw building materials for underground parking lots [56][57][58]. Noteworthily, G4, and G6 showed negative correlations with all the variables, and thus, they could be considered as those showing the best characteristics, the most reassuring from the radiation protection point of view, with the understanding that, as extensively reported above, all of the investigated samples appeared to be nonhazardous to humans.…”
Section: Statistical Featuresmentioning
confidence: 99%
“…In the processed metakaolin minerals group, it can be observed that elements such as Na, Fe, and Ti are present in meagre amounts compared to Al, Si, and O, respectively. [49]. Therefore, it is con rmed that the predominant phase results in silicon dioxide (SiO 2 ) and Aluminium oxide (Al 2 O 3 ) compounds with the addition of other elemental impurities, namely Na, V, Fe, Ti, Mg, Ca, S, etc., [50] which is also consistent with the functional analysis done by FTIR measurements.…”
Section: X-ray Fluorescence Spectroscopymentioning
confidence: 99%
“…After mixing with fly ash at the ratio of 3:2, a geopolymer of 16 MPa was produced at 15 MPa, which demonstrated good environmental stability and leaching toxicity in accordance with the national standard. Meanwhile, the related experiments showed that the geopolymer had better performance in heavy metal curing [22][23][24]. In recent years, even though there have been many attempts to use EMR, the consumption of EMR is still relatively low [25].…”
Section: Introductionmentioning
confidence: 99%